Nutrient Removal and Uptake by Native Planktonic and Biofilm Bacterial Communities in an Anaerobic Aquifer - Lisle, John T. (Frontiers in Microbiology, 2020)
Managed aquifer recharge (MAR) offers a collection of water storage and storage options that have been used by resource managers to mitigate the reduced availability of fresh water. One of these technologies is aquifer storage and recovery (ASR), where surface water is treated then recharged into a storage zone within an existing aquifer for later recovery and discharge into a body of water. During the storage phase of ASR, nutrient concentrations in the recharge water have been shown to decrease due, presumably via the uptake by the native aquifer microbial community. In this study, the native microbial community in an anaerobic carbonate aquifer zone targeted for ASR storage was segregated into planktonic and biofilm communities then challenged with NO3-N, PO4-P and acetate as dissolved organic carbon (DOC) to determine their respective removal and uptake rates. The planktonic community removed NO3-N at a rate of 0.059 mg L-1d-1, PO4-P at 5.73×10-8-1.03×10-7 mg L-1d-1 and DOC at 0.015-0.244 mg L-1d-1. The biofilm community was significantly more proficient, removing NO3-N at 0.116 mg L-1d-1 (1.6-9.0 µg m-2d-1), PO4-P at 4.20-5.91×10-5 mg L-1d-1 (2.47-9.88 ng m-2d-1) and DOC at 0.301-0.696 mg L-1d-1 (29.0-71.0 µg m-2d-1). Additionally, the PO4-P sorption rate onto the carbonate aquifer matrix ranged from 1.64×10-7 to 9.25×10-7 mg PO4-P m-2 day-1. These rates were applied to field data collected at an ASR facility in central Florida and from the same aquifer storage zone from which the biofilm communities were grown. With only 10% of the available surface area within the storage zone being colonized by biofilms, typical concentrations of NO3-N, PO4-P and DOC in the recharged filtered surface waters would be reduced to below detection limits, and by 81.4% and 91.1%, respectively, during a 150 day storage period.